The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0016-7037(03)00214-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of uranyl with the cell wall of Pseudomonas fluorescens inhibits metabolism

Abstract: Abstract-Citric acid is found along with uranyl in the subsurface of former nuclear facilities because of its use as a decontamination agent in the nuclear industry. Citrate's metal chelating properties affect the mobility of uranyl in the subsurface and consequently, citrate biodegradation may significantly impact uranyl fate and transport. Under the non-growth conditions considered, low (micromolar) uranyl concentrations inhibit the biodegradation of citrate by Pseudomonas fluorescens, a common subsurface de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…4) would provide a source of high-affinity U(IV)-binding phosphate sites (52). Phosphate is also released from cell lysis and can precipitate with uranium (14,53). The intimate association of biomass and mackinawite (Fig.…”
Section: S-enriched Hsmentioning
confidence: 99%
“…4) would provide a source of high-affinity U(IV)-binding phosphate sites (52). Phosphate is also released from cell lysis and can precipitate with uranium (14,53). The intimate association of biomass and mackinawite (Fig.…”
Section: S-enriched Hsmentioning
confidence: 99%
“…Soares et al (2002) reported that S. cerevisiae NCNY 1190 releases P when it is exposed to Cd, Cu, and Pb. This release is attributed to uranium or heavy-metal toxicity (Soares et al, 2002;Bencheikh-Latmani and Leckie, 2003). Heavy metals induce lesions of the cell membrane of S. cerevisiae (Joho et al, 1984;Ohsumi et al, 1988), which may cause the cell to rupture.…”
Section: Accumulation Mechanisms Of U(vi) By Yeast S Cerevisiaementioning
confidence: 99%
“…However, no study is known concerning metaautunite formation due to uranium interaction with P. fluorescens strains. To our knowledge, only a few studies provided uranium sorption experiments using P. fluorescens strains (Krueger et al 1993;Bencheikh-Latmani and Leckie 2003;Francis et al 2004;Lütke et al 2012). These studies showed that the strain mainly accumulates uranium on the cell surface, where uranium is bound via protonated phosphoryl and carboxylic sites.…”
Section: Discussionmentioning
confidence: 99%
“…Krueger et al (1993) showed that the strain mainly accumulates uranium on the cell surface. In Bencheikh-Latmani and Leckie (2003), most of the uranyl is also associated with the outside of the cell. Similar results have been obtained by Francis et al (2004), where P. fluorescens was found to accumulate uranium in the periplasm along its plasma and outer membranes as fine-grained, platy uranium-crystals.…”
Section: Introductionmentioning
confidence: 99%